2009
DOI: 10.1002/ange.200900220
|View full text |Cite
|
Sign up to set email alerts
|

Cycle‐Specific Organocascade Catalysis: Application to Olefin Hydroamination, Hydro‐oxidation, and Amino‐oxidation, and to Natural Product Synthesis

Abstract: Teamarbeit: Die kombinierte Anwendung von Iminium(Im)‐ und Enamin(En)‐Katalysatoren ermöglicht eine Vielzahl an wertvollen asymmetrischen Umwandlungen, darunter die 1,2‐Hydroaminierung, 1,2‐Hydrooxidation und 1,2‐Aminooxidation von Olefinen (siehe Bild). Eine enantioselektive Organokaskadenkatalyse wurde auch für die Synthese eines komplexen Naturstoffs genutzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 44 publications
0
19
0
4
Order By: Relevance
“…In 2009, MacMillan et al reported another example of a cycle-specific cascade reaction blending Grubbs catalyst with iminium and enamine catalyst. [28] In this case, the sequential addition of Grubbs II catalyst, iminium catalyst 41 and proline together with the respective addition of 5-hexene-2-one 112, crotonaldehyde 113, and trimethylsilyloxyfuran 114 afforded the desired diastereomer of the product in 64 % yield, 95 % ee with 5:1 dr. It is really striking that from simple starting materials 112-114, the complex skeleton 117 with four stereocenters could be constructed through a one-pot multicatalyst promoted tandem reaction in a very simple operation.…”
Section: By the Combination Of Metal And Organocatalystsmentioning
confidence: 99%
“…In 2009, MacMillan et al reported another example of a cycle-specific cascade reaction blending Grubbs catalyst with iminium and enamine catalyst. [28] In this case, the sequential addition of Grubbs II catalyst, iminium catalyst 41 and proline together with the respective addition of 5-hexene-2-one 112, crotonaldehyde 113, and trimethylsilyloxyfuran 114 afforded the desired diastereomer of the product in 64 % yield, 95 % ee with 5:1 dr. It is really striking that from simple starting materials 112-114, the complex skeleton 117 with four stereocenters could be constructed through a one-pot multicatalyst promoted tandem reaction in a very simple operation.…”
Section: By the Combination Of Metal And Organocatalystsmentioning
confidence: 99%
“…Inherent in any multiple catalyst system is the challenge of compatibility. Avoidance of mutual interference often obliges stepwise addition of catalysts or reagents and variation of reaction conditions over time (21)(22)(23)(24)(25)(26). Nevertheless, cascades triggered by a single operation have been accomplished (20,27,28).…”
mentioning
confidence: 99%
“…These compounds were further transformed to the corresponding chiral 8-membered cyclic hydrazines in moderated to high yields (59-92%) by reaction with Grubb´s catalyst. More challenging it has been the application of a combination of catalysts in cycle-specific organocascade processes [36]. Using this concept, β-methylcinnamaldehyde (32), was converted to product 35 via an amination-hydrogenation sequence using (S)-proline and imidazolidinone 34 as catalysts combination in high yields and excellent diastereo-and enantioselectivities (Scheme 7).…”
Section: Methodsmentioning
confidence: 99%